Expression of Cyclin-D1 in Astrocytes Varies During Aging - Ciapa, Brigitte; Granon, Sylvie (Frontiers in Aging Neuroscience, 2018)
D-cyclins control progression through the G1 phase and the G1/S transition of the cell cycle. In the adult brain, they regulate neurogenesis which is limited to the sub-granular zone (SGZ) of the dentate gyrus (DG) and to the sub-ventricular zone (SVZ) of the lateral ventricles. Yet, D-cyclins have also been detected in other parts of the adult brain in differentiated neurons that do not proliferate and rather die by apoptosis in response to cell cycle reactivation. Expression of D-cyclins in astrocytes has also been reported but published results, such as those concerning neurons, appear conflictual. We carried out this study in order to clarify the general pattern of D-cyclin expression in the mouse brain. By performing GFAP/cyclin-D1 double labeling experiments, we detected hypertrophic astrocytes expressing cyclin-D1 in their cytoplasmic processes. Their number increased with age in the hippocampus area but decreased with age in the SVZ. Clusters of astrocytes expressing cyclin-D1 were also detected in the cortical areas of old mice and around blood vessels of neurogenic areas. Other non-asteroidal small cells, probably stem cells, expressed both GFAP and nuclear cyclin-D1 in the neurogenic area of the DG and in the SVZ at a higher density in young mice than in old mice. Finally, cells expressing cyclin-D1 but not GFAP were also found scattered in the striatum and the CA1 region of the hippocampus, and at a high percentage in cortical layers of young and old mice. Our results suggest that astrocytes may control neuronal functions and proliferation by modulating, in normal or altered conditions such as aging or degenerative diseases, cyclin-D1 expression.